Jak2 Inhibitor AG490 Improved Poststroke Central and Peripheral Inflammation and Metabolic Abnormalities in a Rat Model of Ischemic Stroke - Ya-Yu Wang; Shih-Yi Lin; Cheng-Yi Chang; Chih-Cheng Wu; Wen-Ying Chen; Su-Lan Liao; Yu-Fan Chen; Wen-Yi Wang; Chun-Jung Chen (MDPI AG, 2021)
Poststroke hyperglycemia and inflammation have been implicated in the pathogenesis of stroke. Janus Kinase 2 (Jak2), a catalytic signaling component for cytokine receptors such as Interleukin-6 (IL-6), has inflammatory and metabolic properties. This study aimed to investigate the roles of Jak2 in poststroke inflammation and metabolic abnormality in a rat model of permanent cerebral ischemia. Pretreatment with Jak2 inhibitor AG490 ameliorated neurological deficit, brain infarction, edema, oxidative stress, inflammation, caspase-3 activation, and Zonula Occludens-1 (ZO-1) reduction. Moreover, in injured cortical tissues, Tumor Necrosis Factor-α, IL-1β, and IL-6 levels were reduced with concurrent decreased NF-κB p65 phosphorylation, Signal Transducers and Activators of Transcription 3 phosphorylation, Ubiquitin Protein Ligase E3 Component N-Recognin 1 expression, and Matrix Metalloproteinase activity. In the in vitro study on bEnd.3 endothelial cells, AG490 diminished IL-6-induced endothelial barrier disruption by decreasing ZO-1 decline. Metabolically, administration of AG490 lowered fasting glucose, with improvements in glucose intolerance, plasma-free fatty acids, and plasma C Reactive Proteins. In conclusion, AG490 improved the inflammation and oxidative stress of neuronal, hepatic, and muscle tissues of stroke rats as well as impairing insulin signaling in the liver and skeletal muscles. Therefore, Jak2 blockades may have benefits for combating poststroke central and peripheral inflammation, and metabolic abnormalities.